Impact of Communication and Information Technology on Finance and Human Capital in Government Systems - Priyanto, Eddy; Sulisnaningrum, Ema; Murniati, Murniati (Asia Pacific Journal of Management and Education (APJME), 2023)
The purpose of this study is to analyze the relationship between topics, namely: Finance, Information and Communication Technology, the need of ICT, and the impact of information and communication technology on finance. Qualitative Research Methods using Content Analysis to compile scientific articles from emerald and Korean science as well as books written by ICT and Financial Information experts. It is known that the government system has an impact on government regulations and policies related to the financial system. The government system influences operational processes and developments in financial technology. Not only that, but the government system also determines the education system, which has an impact on developing the quality of human resources. Technology and information play a significant role in economic growth, financing, and human needs, so they have become essential in human life, including finance and human resource development. The community needs current and future information and communication technology (ICT) capabilities to be productive in today's f work. The value of this research is the application of technology to e-finance and the emergence of e-finance that can be applied to the banking business and financial services.